2008
DOI: 10.1111/j.1740-8261.2008.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Left Heart Base Descent in Dogs With Dilated Cardiomyopathy and Normal Dogs

Abstract: The identification and assessment of myocardial failure in canine idiopathic dilated cardiomyopathy (DCM) is achieved using a variety of two-dimensional and Doppler echocardiographic techniques. More recently, the availability of tissue Doppler imaging (TDI) has raised the potential for development of new ways of more accurately identifying a disease phenotype. Nevertheless, TDI has not been universally adapted to veterinary clinical cardiology primarily because of the lack of information on its utility in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…They observed that the intervals Q-beginning of S′, Q-end of S′ were extended and the maximum velocity of S′ was reduced in dogs with dilated cardiomyopathy. The S′ duration was not affected by the systolic dysfunction [43]. …”
Section: Timing Of Left Heart Base Descentmentioning
confidence: 73%
See 1 more Smart Citation
“…They observed that the intervals Q-beginning of S′, Q-end of S′ were extended and the maximum velocity of S′ was reduced in dogs with dilated cardiomyopathy. The S′ duration was not affected by the systolic dysfunction [43]. …”
Section: Timing Of Left Heart Base Descentmentioning
confidence: 73%
“…These are the left heart base descent time intervals [43]. To obtain these time intervals, the S′ wave of the base of the interventricular septum or left ventricular free wall must be recorded using TDI.…”
Section: Timing Of Left Heart Base Descentmentioning
confidence: 99%
“…Patients with intraventricular dyssynchrony were, independent of QRS width and EF, at significantly higher risk of cardiac events, 48,49 and LV systolic and diastolic mechanical dyssynchrony is reported to be common in patients with CHF 50 . Systolic velocity time‐to‐peak was longer in the lateral wall compared with that of IVS in dogs with DCM 9 …”
Section: Discussionmentioning
confidence: 99%
“…2 Tissue Doppler imaging (TDI) has been extensively evaluated in healthy dogs and in dogs with different heart diseases. [7][8][9][10][11][12][13] This relatively new technique allows quantitative assessment of segmental and global myocardial radial and longitudinal motion in systole and diastole, as well as accurate timing of events in relation to the QRS complexes on ECG recordings. TDI variables have been reported in dogs with MMVD and concomitant pulmonary hypertension.…”
mentioning
confidence: 99%
“…115,192,263,307,311,312,[468][469][470][471][472] Atrioventricular valve insufficiency is usually present (see Figure 8-52; Video 8-36, B to D), although the regurgitation is often mild when compared to dogs with primary valvular disease or to cats with diuretic therapy, especially if a precipitating cause is identified and reversible. 115,192,263,307,311,312,[468][469][470][471][472] Atrioventricular valve insufficiency is usually present (see Figure 8-52; Video 8-36, B to D), although the regurgitation is often mild when compared to dogs with primary valvular disease or to cats with diuretic therapy, especially if a precipitating cause is identified and reversible.…”
Section: Doppler Studiesmentioning
confidence: 99%